1998
DOI: 10.2135/cropsci1998.0011183x003800060048x
|View full text |Cite
|
Sign up to set email alerts
|

DNA‐Based Markers for a Recessive Gene Conferring Anthracnose Resistance in Sorghum

Abstract: Resistance to anthracnose in sorghum [Sorghum bicolor (L.) Moench] accession SC326‐6 was found to segregate as a simple recessive trait in a cross to the susceptible cultivar BTx623.F3 progeny tests following self pollination of 115 F2 individuals identified homozygous resistant and susceptible F2 plants for use in bulked‐segregant analysis. DNA from the parental cultivars and the bulks was screened by PCR amplification with 300 RAPD (random amplified polymorphic DNA) primers. Two RAPD primers amplified a sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 0 publications
3
23
0
Order By: Relevance
“…Resistance to isolate 1 was mainly due to dominant alleles that confered vertical resistance but also by incomplete dominance alleles (hybrids 121, 122, 133, 134 and 138) and recessive alleles (hybrids 98 and 112), by comparing the genitors and hybrids infection scores to those that present both information.. In many cases, alleles that confered resistance to isolate 11 (Jataí) were recessive (hybrids 95, 98, 99, 103, 104, 106, 108, 110, 113, 118, 119, 121, 122, 134 and 150), which is in accordance with studies done by Boora et al (1998), Mehta et al (2005) and Singh et al (2006). Hybrid 93 was the only three-way hybrid tested.…”
Section: Resultssupporting
confidence: 84%
“…Resistance to isolate 1 was mainly due to dominant alleles that confered vertical resistance but also by incomplete dominance alleles (hybrids 121, 122, 133, 134 and 138) and recessive alleles (hybrids 98 and 112), by comparing the genitors and hybrids infection scores to those that present both information.. In many cases, alleles that confered resistance to isolate 11 (Jataí) were recessive (hybrids 95, 98, 99, 103, 104, 106, 108, 110, 113, 118, 119, 121, 122, 134 and 150), which is in accordance with studies done by Boora et al (1998), Mehta et al (2005) and Singh et al (2006). Hybrid 93 was the only three-way hybrid tested.…”
Section: Resultssupporting
confidence: 84%
“…This was confirmed by Erpelding (2007), who reported a single dominant gene conferring resistance to the foliar phase of anthracnose in sorghum cultivar Redlan. Tenkouano (1993), quoted by Perumal et al (2009), revealed a single genetic locus with multiple allelic forms conferring resistance to anthracnose in SC326-6 while Boora et al (1998) revealed that resistance to anthracnose in SC326-6a is encoded by single recessive gene. This suggested the need to look for additional sources of resistance in order to identify more genes that code for anthracnose resistance.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that resistance to the anthracnose stages to leaf and stalk rot is under independent genetic control (Casela et al, 1997). LeBeau and Coleman (1950) verified that the resistance is controlled by recessive genes, which was confirmed by the studies by Singh et al (2006) and Boora et al (1998) using RAPD and SCAR markers for sorghum lineages. In other studies, the inheritance of resistance was reported to be determined by a larger number of genes with partial dominance or an additive effect; by a dominant gene without cytoplasmic influences; or by a single locus with multiple alleles (Murty and Thomas, 1989;Tenkouano and Miller, 1993).…”
Section: The Genetics Of Anthracnosementioning
confidence: 78%
“…Tenkuano et al (1993a,b) proposed selection at the seedling stage based on phytoalexin content. Recently, markers linked to anthracnose resistance have been identified (Boora et al, 1998). The molecular markers make the pyramiding of genes feasible and the genes be more stable across environments.…”
Section: Genomic Selection For Anthracnose Resistancementioning
confidence: 99%
See 1 more Smart Citation